Environmental governance: urban community-driven conservation endeavors in the Cape - Horn, Inca (Department of Environmental and Geographical Science, 2025)
Conservation of ecosystems on all scales is important, especially in light of the Anthropocene. The Cape is an important site for biodiversity and is home to many people and ecosystems. The ecosystems in urban environments influence the well-being of communities and provide essential services. Conservation in the urban is part of a complex socio-ecological system, and governance is an important factor in ensuring effective decisions are made and appropriate management actions taken. Although there are clear guidelines for conservation on a national and provincial level, it is less clear for civic and urban efforts. This research aims to establish how local conservation endeavors are governed in the urban Cape and how this governance aligns to policies in South Africa. The purpose is to provide insights into gaps in information and policy. Three cases of community driven conservation endeavors were identified for exploration in the urban areas of the Cape Floristic Region. This research uses the framework for environmental governance by Bennett and Satterfield (2018) to uncover the rich material of urban green space conservation, which is presented against the backdrop of relevant policies. It is important to determine how these spaces are governed on the ground, and if this framework is a useful tool to extract and use information on this scale. Based on the framework for effective conservation governance, data was collected through semi-structured interviews with eight people involved in the identified endeavors. The interviewees included members of the municipalities, endeavor managers and civilian volunteers. A policy analysis of environmental governance in South Africa was done to determine the guidelines in which these endeavors should operate, and to identify the objectives that the cases are meeting. Data from interviews was used to uncover the governance modes, common themes, and effectiveness of local environmental conservation. Urban conservation fulfills many social and environmental goals when governed effectively. These conservation endeavors create outputs which align with important national goals, and the Sustainable Development Goals for life on land and sustainable cities and communities. Community support and good relationships in local government proved to be the most critical to effective governance. These cases do not operate within clear policy guidelines, and their governance modes differ depending on the local socio ecological context. These findings support the need for bottom-up governance, community led conservation and strong relationships between civic society and government to meet social and environmental goals in the urban.